Tooth fragment reattachment : evaluation of fracture resistance using intermediate materials versus direct composite restoration - Pereira, Raquel Vitório (2020)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Ciências da Saúde, Departamento de Odontologia, Programa de Pós-Graduação em em Odontologia, 2020.